Pandangan Ulama dan Tenaga Kesehatan di Sumedang Terhadap Kontrasepsi Permanen Tanpa Indikasi Medis - Selma Nuraeni; Anestia Nur Hanifa; Muhammad Naufal Lukmanul Hakim; Pina Permata Pratiwi; Sandrina Fitriani; Tyas Syahdina Putri; Tedi Supriyadi; Akhmad Faozi (Universitas Galuh, 2025)
The use of permanent sterilization contraception, such as vasectomy and tubectomy, remains a sensitive issue among Indonesian Muslims, particularly in Sumedang Regency. This study aims to explore the views of Islamic scholars (ulama) and health workers on the practice of permanent sterilization without medical indications. This study used a qualitative case study approach with semi-structured interviews with five informants: two ulama, two health workers, and one community leader who was also a sterilization patient. The results indicate that Islamic scholars reject permanent sterilization without medical reasons because they are considered contrary to the principles of the maqasid sharia, specifically preserving offspring (hifz al-nasl). In contrast, health workers accept the procedure if accompanied by medical indications and the consent of the partner. These differing views reflect differing perspectives on sterilization, family planning, and couple readiness. This study used an educational approach and interdisciplinary dialogue between religious leaders and health workers to bridge the gap. Practical implications: education that combines sharia values with reproductive health information is crucial to help communities make informed, rational contraceptive decisions that align with local spiritual and cultural values.